Focuses and trends of the studies on pediatric palliative care：A bibliometric analysis from 2004 to 2018 - Miao Zhang; Xiaohan Li (Elsevier, 2021)
Objectives: To investigate the focuses and trends of the studies on pediatric palliative care (PPC) and provide directions for future research. Methods: Relevant papers about PPC published from 2004 to 2018 were analyzed using bibliometric analysis methods, including co-word analysis, biclustering analysis, and strategic diagram analysis. The included papers were divided into three groups based on the publication time, including 2004-2008, 2009-2013, and 2014-2018. Results: A total of 1132 papers were published between 2004 and 2018, and there were 293 papers published between 2004 and 2008, 396 between 2009 and 2013, and 443 between 2014 and 2018. There were 42 high-frequency MeSH terms/MeSH subheadings in papers published between 2004 and 2018, including 12 between 2004 and 2008, 13 between 2009 and 2013, and 17 between 2014 and 2018. Conclusion: Studies on PPC were making progress, with the increasing number, expanding scope, and uneven global distribution. Integration palliative care into pediatrics, cancer treatments in pediatric oncology, education methods on PPC, and establishment of professional teams were the major themes during 2004-2008, then the themes changed into establishing interventions to enhance the quality of life of the patients and parents, building professional-family relationship, and investigating attitude of health personnel in PPC during 2009-2013 and subsequently turned into communication skills, end-of-life decision making, and guidelines making on PPC during 2014-2018. Underdeveloped and protential themes including effective approaches to deal with the ethical dilemmas, training programs on communication skills, family support and guideline making are worth studying in the future.